Rahn Over Murabahah Objects In BSI Gold Installment Products: A Shafi‘I Fiqh Analysis - Musthafa Syukur; Ramdani (CV Putra Publisher, 2026)
The rapid growth of Islamic banking in Indonesia has encouraged the development of hybrid financing products, including the Gold Installment product offered by Bank Syariah Indonesia (BSI). This product combines murābaḥah (cost-plus sale) and rahn (pledge) contracts, in which the gold purchased by the customer is retained by the bank as collateral until all installments are paid. Although widely implemented, the validity of this contractual structure remains debated in Islamic jurisprudence, particularly regarding ownership (al-milk al-tām) and possession (qabḍ). This study aims to analyze the legal validity of rahn over the object of murābaḥah from the perspective of Shafi‘i fiqh. Using a qualitative library research approach, this study examines classical Shafi‘i legal texts, DSN-MUI fatwas, regulatory documents, and recent scholarly literature. The analysis shows that the use of the same gold as both the object of sale (mabī‘) and collateral (marhūn) raises significant juridical concerns. According to Imam al-Nawawī and other Shafi‘i jurists, a rahn contract is valid only when the pledgor has complete ownership and effective possession of the pledged asset. These conditions are not fully satisfied when the gold remains under the bank’s control from the outset of the financing. The study contributes to the literature by providing a focused normative analysis from the Shafi‘i madhhab, an area that has received limited attention in previous studies. It recommends restructuring the contract mechanism by ensuring qabḍ prior to rahn and by separating the sale object from the collateral. Such adjustments would strengthen both Sharī‘ah compliance and operational integrity in Islamic banking.